Artificial Intelligence in Biological Fields: Innovations and Practical Applications - Celayir, Nasrullah; Aslan, Abdullah (Fırat Üniversitesi, 2025)
The use of artificial intelligence in the biomedical field is a field that has developed rapidly and has transformative potential in recent years. This study aims to reveal the potential of artificial intelligence to offer innovative solutions in healthcare by examining its role in biomedical research and applications. The use of artificial intelligence in the biomedical field is effective in a wide range of areas from early diagnosis of diseases to the creation of treatment plans. The opportunities offered by artificial intelligence in the analysis and interpretation of biomedical data enable faster and more accurate diagnoses. Machine learning algorithms, in particular, help us better understand the symptoms and pathological processes of diseases by analyzing large data sets. In this way, doctors and researchers can predict the progression of diseases and develop more effective treatment methods. Artificial intelligence also has a great impact on the field of medical imaging. Image processing algorithms reach high accuracy rates in detecting abnormalities in X-ray, MRI (Magnetic Resonance Imaging) and CT (Computed Tomography) scans, reducing the workload of radiologists and accelerating diagnostic processes. These technologies are also used in surgical planning and minimally invasive surgeries. In summary, this study aims to compile current technologies used in the biomedical field of artificial intelligence and to identify new and unique areas of use inspired by these technologies.

Yapay zekanın biyomedikal alandaki kullanımı, son yıllarda büyük bir hızla gelişen ve dönüştürücü potansiyele sahip bir alandır. Bu çalışma, yapay zekanın biyomedikal araştırma ve uygulamalardaki rolünü inceleyerek, sağlık hizmetlerinde yenilikçi çözümler sunma potansiyelini ortaya koymayı amaçlamaktadır. Yapay zekanın biyomedikal alanda kullanımı, hastalıkların erken teşhisinden, tedavi planlarının oluşturulmasına kadar geniş bir yelpazede etkili olmaktadır. Biyomedikal verilerin analizi ve yorumlanmasında yapay zekanın sunduğu olanaklar, daha hızlı ve doğru teşhisler konulmasını sağlamaktadır. Özellikle makine öğrenimi algoritmaları, büyük veri setlerini analiz ederek, hastalıkların belirtilerini ve patolojik süreçlerini daha iyi anlamamıza yardımcı olmaktadır. Bu sayede, doktorlar ve araştırmacılar, hastalıkların ilerleyişini öngörebilir ve daha etkili tedavi yöntemleri geliştirebilirler. Tıp görüntüleme alanında da yapay zekanın etkisi büyüktür. Görüntü işleme algoritmaları, röntgen, MR (Manyetik Rezonans Görüntüleme) ve CT (Bilgisayarlı tomografi) taramalarındaki anormallikleri tespit etmede yüksek doğruluk oranlarına ulaşarak, radyologların iş yükünü azaltmakta ve teşhis süreçlerini hızlandırmaktadır. Bu teknolojiler, aynı zamanda, cerrahi planlama ve minimal invaziv cerrahilerin gerçekleştirilmesinde de kullanılmaktadır. Özetle bu çalışma yapay zekanın biyomedikal alanda kullanılan güncel teknolojilerini derlemeyi ve bu teknolojilerden ilham alarak yeni ve özgün kullanım alanlarını tespit etmeyi hedefler.
Biyolojik Alanlarda Yapay Zeka: İnovasyonlar ve Pratik Uygulamalar
Keywords: Genomics; Genomik